العمارة المدنية في مدينة طبنه خلال العهد الروماني – دراسة أثرية – - مياطة, التجاني (University of Eloued جامعة الوادي, 2022)
: يعد النموذج العمراني الروماني القائم على أسس فكرية مرتكزة على تصور العالم المدني الخاضع لروما على أنه أمثلة مكررة لنسخة أصلية تشكلت عناصرها في روما نفسها، و من الأدلة الواضحة على ذلك هي الخصائص المميزة لعمران الروماني الملاحظ في صور متكررة عبر المقاطعات، بحيث لم تختلف نماذج العمارة فيها سواء كانت مدنية أو عسكرية، من حيث الشكل أو مادة البناء المستعملة أما بناياتها الوظيفية فهي موحدة و تستجيب لمفاهيم مدنية وثقافية واحدة، ومن أمثلة المنشآت المدنية التي ظهرت و ازدهرت في إقليم الحضنة تحت السيطرة الرومانية مدينة طبنه وما صاحب ذلك من أعمال الري. Abstract: The Roman urban model based on intellectual foundations based on the perception of the civil world under Rome as replicated examples of an original version whose elements were formed in Rome itself, and clear evidence of this are the distinctive characteristics of Roman urbanization observed in repeated images across the provinces, so that the models of architecture did not differ In it, whether civilian or military, in terms of shape or building material used, as for its functional structures, they are unified and respond to one civil and cultural concepts. Examples of civil facilities that appeared and flourished in the province of Al-Hudna under the Roman control are the city of Tabna and the irrigation works that accompanied that, given that this is one of the manifestations of vitality that arose in some of the provinces of Al-Lims.
مقال
Keywords: الكلمات المفتاحية: العمارة المدنية، روما، الليمس، مدينة طبنه، الأثار، الحضنة. ; key words: Civil architecture, Rome, Al-Limes, Tabna city, antiquities, Al-Hadna.